Evaluation of Irisin Level in Iraqi Patients with Type 2 Diabetes and Pre-Diabetes Status as a Predictive Factor - Mohammed Hatem , Hiba; Khudhair Ghudhaib , Kadhim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The prevalence of diabetes is increasing rapidly and is now recognized as a significant global health problem. Diabetes occurs when a person does not produce enough insulin due to an imbalance in insulin production. This can lead to the failure of organs and tissues such as the kidneys, heart, blood vessels, eyes, nerves, and kidneys. As a result, early diagnosis and classification of type 2 diabetes mellitus (T2DM) are critical to aiding physician assessments. Subsequently, the current study aims to determine irisin levels in patients with T2DM and pre-DM as early predictors for disease cases. The current study included 138 subjects divided into three groups based on fasting blood glucose (FBG) and glycosylated hemoglobin criteria, including T2DM, 46 patients, pre-diabetes, 46 participants, and healthy subject groups, 46 persons) when they enrolled in the National Diabetes Center/ Al-Mustansiriya University. Enzyme-linked immunosorbent assays were used to detect the levels of irisin and insulin, and spectrophotometric techniques were used to determine the levels of FBG and lipid profile. The results of irisin revealed significant differences among the studied groups. Also, the insulin results showed substantial differences between the diabetic and control groups. Moreover, the results of HOM-IR and HOMA-IS and lipid profiles showed significant differences between the studied groups. The results showed that irisin can serve as an early indicator of pre-diabetes. These results were reinforced by the results of the ROC analysis, which indicated that irisin is an excellent indicator for diagnosing the studied condition.